Strategi Guru Dalam Pembelajaran Pendidikan Agama Islam Bagi Anak Berkebutuhan Khusus - Arif, Muhamad; Nurva’izah, Silvy; Abd Aziz, Mohd Kasturi Nor bin (Universitas Yudharta Pasuruan, 2023)
This study discusses teacher strategies for learning Islamic religious education in children with special needs (case studies in SMPLB Negeri Cerme). This study aims to find out the teacher's strategy for learning Islamic religious education in mentally retarded children in Cerme State Middle School and to identify supporting and inhibiting factors in the implementation of Islamic Religious Education Learning Strategies in Tabenagrahita Children in Cerme State Middle School. This type of research is descriptive-qualitative with a case study approach. Data collection techniques used are observation, interviews, and documentation methods. Data analysis techniques using Milles and Huberman theories, namely data reduction, data presentation, data validity, and drawing conclusions, The results of this study indicate that the strategy implemented by Islamic Religious Education teachers in Cerme State Middle School for children with Tabenagrahita is a discovery learning strategy. Learning with Discovery Learning strategies is centered on students and educators only as a companion and helps students if they find difficulties during the learning process. Discovery learning strategies make students active learners because educators provide the opportunity to ask questions, argue, and find their own answers to a problem. As seen in the learning steps of discovery learning that have been carried out by educators in the learning process, which starts with stimulation, problem statement, data collection, data processing, verification, and generalization, Of course, in the application of learning strategies, there are supporting and inhibiting factors, as follows: supporting factors, interests, and motivation of educators, as well as the communication of teachers and parents of students. Inhibiting factors, concentration of learning, obstructing language development, the condition of mental retardation, children who are easy to forget, and educators are not graduates of extraordinary education.